A Study of CPU Scheduling Techniques in Comparison (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
Due to the requirement to alter and test operating system kernel code and assess the resultingperformance on a consistent workload of real applications, developing CPU schedulingmethods and understanding their impact in practice can be challenging and time consuming.Because the processor is such a valuable resource, CPU scheduling is critical for achievingthe operating system (OS) design goals. The goal should be to keep as many processes activeas possible at all times in order to get the most out of the CPU. The primary goal of CPUscheduling is to improve the computer's performance. The amount of time spent waiting has asignificant impact on the performance and execution time of a computer system. It's mucheasier to grasp what's going on inside the system with this representation, and why a differentcollection of processes is a candidate for CPU allocation at different periods. The study's goalis to examine the highly efficient CPU scheduler's impact on the design of high-qualityscheduling algorithms that meet the scheduling goals. It is mostly focused on reducingwaiting times and turn-around times in order to improve a computer system's level ofperformance. Many CPU scheduling methods exist, however due to high context switch rates,long waiting times, long response times, long turnaround times, and low throughput; theycannot be applied in real-time operating systems.